Genetic and ecophysiological evidence that hybridization facilitated lineage diversification in yellow Camellia (Theaceae) species: a case study of natural hybridization between C. micrantha and C. flavida - Sujuan Wei; Qiwei Zhang; Shaoqing Tang; Wenbo Liao (BMC Plant Biology, 2023)
Abstract Background Hybridization is generally considered an important creative evolutionary force, yet this evolutionary process is still poorly characterized in karst plants. In this study, we focus on natural hybridization in yellow Camellia species, a group of habitat specialists confined to karst/non-karst habitats in southwestern China. Results Based on population genome data obtain from double digest restriction-site associated DNA (ddRAD) sequencing, we found evidence for natural hybridization and introgression between C. micrantha and C. flavida, and specifically confirmed their hybrid population, C. “ptilosperma”. Ecophysiological results suggested that extreme hydraulic traits were fixed in C. “ptilosperma”, these being consistent with its distinct ecological niche, which lies outside its parental ranges. Conclusion The identified hybridization event is expected to have played a role in generating novel variation during, in which the hybrid population displays different phenological characteristics and novel ecophysiological traits associated with the colonization of a new niche in limestone karst.